Formulation, Optimization And Evaluation Of Spray Dried Microspheres Of Azithromycin Dihydrate - MAULIK A. ACHARYA,; MANDEV B. PATEL,; ANIL BHANDARI, (International Journal of Pharma and Bio Sciences, 2012)
In the present study formulation and characterization of spray drying microspheres of azithromycin dihydrate, (prescribed extensively in solid dosage forms) in a sustained release form to overcome drug resistance, and dosing non-compliance in pediatric patients. So, the purpose of this research was to formulate sustained release microspheres of azithromycin dihydrate using chitosan as a carrier polymer, which is also a suitable polymer to mask the bitter taste of drug. Drug entrapment efficiency for azithromycin dihydrate reached to highest level of 84.8% and percentage yield to 68%. Formulated spray dried microspheres gave drug release for the initial dosing and maintenance dosing in a sustained manner for 72 hours. This gave a hope to the possibility of single dose treatment for pediatric patients. The formulated microspheres show pharmacotechnical properties in the acceptable range.